MoN / TiN nanotube / lithium iron phosphate composite material and its preparation and application

By composite calcining the lithium iron phosphate material with MoN/TiN nanotubes, the poor performance of lithium iron phosphate material under low temperature and high magnification conditions was solved, and its low temperature and magnification performance was significantly improved.

CN119742324AInactive Publication Date: 2025-04-01JIANGXI HESHENG HUILI NEW ENERGY CO LTD

Patent Information

Application Number
CN202411761132.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The poor conductivity of lithium iron phosphate materials leads to poor performance under low temperature and high magnification conditions, especially at low temperatures with low reversible cycle capacity.

Method used

By compositely calcining the lithium iron phosphate material with MoN/TiN nanotubes, the interfacial lithium ion diffusion rate is improved, the diffusion barrier of Li+ is reduced, and the diffusion rate of Li+ is increased.

Benefits of technology

It significantly improves the low temperature and rate performance of lithium iron phosphate materials, and improves its discharge capacity and cycling performance at low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742324A_ABST
    Figure CN119742324A_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of positive electrode materials, and specifically relates to a method for preparing a MoN / TiN nanotube / lithium iron phosphate composite material, which is obtained by mixing a lithium iron phosphate material and a MoN / TiN nanotube and calcining them at a temperature of 300 to 700°C. The present invention also provides a material obtained by the preparation method and its application. The present invention innovatively calcines the lithium iron phosphate material and the MoN / TiN nanotubes, which can improve the lithium ion diffusion rate at the lithium iron phosphate interface, reduce the diffusion barrier of Li+, and increase the Li+ diffusion rate, thereby significantly improving the low-temperature fast charging performance of LFP.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery positive electrode materials, and in particular relates to a lithium ion positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium iron phosphate is one of the mainstream lithium-ion positive electrode materials. It has the advantages of low cost, environmental protection, good safety, and long cycle life. It is particularly suitable for application fields such as new energy vehicle power batteries and energy storage batteries. At present, lithium iron phosphate occupies a dominant position in the lithium-ion battery positive electrode material industry.

[0003] One of the main disadvantages of lithium iron phosphate is its poor electrical conductivity, which makes it only suitable for charging and discharging at low current density, with poor rate performance, especially at low temperatures, and low reversible cycle capacity. In order to improve the low temperature and rate performance of lithium iron phosphate, the existing technology optimizes the electronic and ionic conductivity by means of element doping modification or carbon coating.

[0004] For example, the Chinese patent document with publication number CN108598383A discloses a method for preparing a Ti and N co-doped spherical lithium iron phosphate composite material, wherein a lithium source, an iron source, a phosphate and titanium nitride are mixed in a certain element molar ratio to obtain a mixture, a soluble carbon source is added to the mixture, and the mixture is mixed and coarsely ground and finely ground to a specified slurry particle size in a liquid medium, and then spherical drying and granulation are performed using a spray drying technology, and finally the dried spray material is subjected to three-stage gradient sintering in an atmosphere furnace to finally obtain a Ti and N co-doped spherical lithium iron phosphate composite material (LiFe1-XTixPO4-xNx / C). The Chinese patent document with publication number CN108091851A discloses a lithium iron phosphate composite positive electrode material and its preparation method and application, wherein an organic carbon source and a highly conductive phase titanium nitride are simultaneously introduced by spray drying to prepare a lithium iron phosphate composite positive electrode material, and a lithium iron phosphate composite positive electrode material with high conductivity, uniform particles, high tap density and a multi-level structure is obtained. A Chinese patent document with publication number CN104124437A discloses a lithium iron phosphate composite positive electrode material with titanium nitride and graphene coated on the surface, a preparation method thereof, and an application in the preparation of lithium-ion batteries. The lithium iron phosphate composite positive electrode material is based on a lithium iron phosphate material as a core, and a conductive network film mainly composed of titanium nitride and graphene is coated on the surface of the lithium iron phosphate material; the mass of the conductive network film is 0.2% to 10% of the mass of the lithium iron phosphate material.

[0005] The above methods only form crystal defects through doping to improve the ionic and electronic conductivity of the material itself. They are still not ideal for improving the low-temperature and rate performance of the material. The low-temperature and fast-charging performance of the material needs to be further improved. Summary of the invention

[0006] In view of the shortcomings of existing lithium iron phosphate materials, the first purpose of the present invention is to provide a method for preparing a MoN / TiN nanotube / lithium iron phosphate composite material, aiming to prepare a positive electrode active material with excellent low-temperature fast charging performance.

[0007] The second purpose of the present invention is to provide a MoN / TiN nanotube / lithium iron phosphate composite material prepared by the preparation method and its application.

[0008] The third object of the present invention is to provide a lithium-ion battery comprising the MoN / TiN nanotube / lithium iron phosphate composite material and a positive electrode and a positive electrode material thereof.

[0009] The preparation method of MoN / TiN nanotube / lithium iron phosphate composite material comprises the following steps: mixing lithium iron phosphate material and MoN / TiN nanotube and calcining the mixture at a temperature of 300-700 DEG C.

[0010] The present invention innovatively composite-calcines lithium iron phosphate material and MoN / TiN nanotubes, which can improve the lithium ion diffusion rate at the lithium iron phosphate interface, reduce the diffusion barrier of Li+, and increase the Li+ diffusion rate, thereby significantly improving the low-temperature fast charging performance of LFP.

[0011] In the present invention, the lithium iron phosphate material may be a lithium iron phosphate material obtained in any manner, for example, it may be carbon composite lithium iron phosphate.

[0012] In an optional manner of the present invention, the lithium iron phosphate material is obtained by sintering a mixture containing an iron source, a lithium source, a phosphorus source, and a carbon source.

[0013] In the present invention, MoN / TiN nanotubes are innovatively used to carry out calcination modification of lithium iron phosphate, so that the physical and chemical structure of the material can be optimized based on the combination of its composition and special physical and chemical structure, and the low-temperature fast charging performance of the prepared material can be significantly improved.

[0014] In the present invention, the MoN / TiN nanotube is a hollow tubular material formed by the composite of MoN and TiN, wherein the thickness of the tube is 5 to 30 nm, the diameter of the tube is 50 to 120 nm, and the length of the tube is 150 to 500 nm.

[0015] In the present invention, in the MoN / TiN nanotubes, the weight ratio of MoN / TiN is 0.01 to 0.1:1, and can further be 0.03 to 0.05:1.

[0016] In the present invention, the MoN / TiN nanotubes are obtained by mixing nano MoN particles and TiN nanotubes and then heat treating them at 500-900°C (preferably 750-850°C), wherein the heat treatment time is 4-10 hours (preferably 6-7 hours).

[0017] In the present invention, the weight ratio of lithium iron phosphate to MoN / TiN nanotubes in the lithium iron phosphate material is 1:0.005-0.1.

[0018] Preferably, the lithium iron phosphate material and the MoN / TiN nanotubes are composited in a solid phase or liquid phase manner.

[0019] In the present invention, the calcination atmosphere is a protective atmosphere, for example, it may be at least one of nitrogen and an inert gas.

[0020] Preferably, the lithium iron phosphate material and the MoN / TiN nanotubes are composited by a liquid phase method using an organic solvent such as methanol or ethanol;

[0021] Preferably, the calcination temperature is 400 to 600°C, and further preferably 500 to 550°C.

[0022] Preferably, the holding time at the calcination temperature is 2 to 8 hours, further 5 to 6 hours.

[0023] The invention also provides a MoN / TiN nanotube / lithium iron phosphate composite material prepared by the preparation method.

[0024] The method described in the present invention can give the prepared material special physical and chemical characteristics, and the MoN / TiN nanotube / lithium iron phosphate composite material with the characteristics prepared by the preparation method can show excellent electrochemical properties, for example, can show excellent low-temperature fast charging performance.

[0025] The present invention also provides an application of the MoN / TiN nanotube / lithium iron phosphate composite material, which is used as a positive electrode active material for preparing a lithium ion battery.

[0026] In the present invention, based on known principles and means, the MoN / TiN nanotube / lithium iron phosphate composite material of the present invention can be used as a positive electrode active material to prepare the required lithium ion battery and its positive electrode and positive electrode material.

[0027] The present invention also provides a lithium ion battery, which comprises the MoN / TiN nanotube / lithium iron phosphate composite material prepared by the preparation method;

[0028] Preferably, the positive electrode of the lithium-ion battery comprises the MoN / TiN nanotube / lithium iron phosphate composite material.

[0029] Beneficial effects:

[0030] MoN / TiN nanotubes are calcined and cross-linked to wrap nano-lithium iron phosphate, which improves the lithium ion diffusion rate at the lithium iron phosphate interface, reduces the diffusion barrier of Li+, and increases the Li+ diffusion rate, thereby significantly improving the low temperature and rate performance of LFP. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope image of the MoN / TiN nanotube cross-linked and wrapped nano lithium iron phosphate material obtained in Example 1; DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0033] The invention discloses a lithium iron phosphate positive electrode material, comprising lithium iron phosphate and surface composite MoN / TiN nanotubes.

[0034] The steps for preparing the material of the present invention include, for example:

[0035] S1. Weigh iron source, lithium source, phosphorus source and carbon source in a molar ratio of Li:Fe:P:C=(1-1.1):1:(1-1.06):(0.05-0.6), disperse them in deionized water and mix them evenly, then perform sand milling, spray drying and sintering to obtain a lithium iron phosphate matrix.

[0036] S2. According to the mass ratio of MoN to TiN of 0.01 to 0.1:1, nano MoN particles and TiN nanotubes are mixed, and heat treated at 500 to 900° C. for 4 to 10 hours to obtain MoN / TiN nanotubes. The TiN nanotubes are commercial products or prepared by conventional means.

[0037] S3, mixing the lithium iron phosphate matrix prepared in step S1 with the pre-dispersed MoN / TiN nanotubes, stirring and drying, and then continuing to calcine under a protective atmosphere and cooling to room temperature to obtain MoN / TiN nanotube cross-linked wrapped nano lithium iron phosphate positive electrode material.

[0038] In step S1, the iron source is at least one of ferric phosphate, ferrous phosphate, ferrous oxalate, and ferric oxide; the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium phosphate, lithium acetate, and lithium nitrate; the phosphorus source is at least one of phosphoric acid, lithium phosphate, lithium dihydrogen phosphate, lithium monohydrogen phosphate, ammonium phosphate, diammonium phosphate, and monoammonium hydrogen phosphate; and the carbon source is at least one of polyethylene glycol, glucose, sucrose fructose, lactose, soluble starch, phenolic resin, polyacrylic acid, and chitosan.

[0039] The solvent used for dispersing the pre-dispersed MoN / TiN nanotubes is at least one of deionized water, methanol and ethanol, and the mass ratio of the MoN / TiN nanotubes to the dispersant is 0.01-0.1:1.

[0040] The mass ratio of the lithium iron phosphate matrix to the MoN / TiN nanotubes in step S3 is 1:0.005-0.1.

[0041] The MoN / TiN nanotubes in step S3 have a thickness of 5 to 30 nm, a tube diameter of 50 to 120 nm, and a tube length of 150 to 500 nm.

[0042] The mixing and stirring time in step S3 is 0.5 to 2 hours, and the drying method is spray drying.

[0043] The protective atmosphere in step S3 is nitrogen or argon atmosphere, the calcination temperature is 300-700° C., and the calcination time is 2-8 hours.

[0044] The following are more typical implementations:

[0045] In the present invention, the selected lithium iron phosphate material can be a conventional commercial product, or can be prepared based on conventional means. For example, in the following case, as an optional method, the lithium iron phosphate is prepared by the following steps:

[0046] Lithium carbonate, iron phosphate, ammonium dihydrogen phosphate and glucose (carbon source) are weighed separately according to the molar ratio of Li:Fe:P:C (carbon source) = 1.04:1:1.04:0.55 for preparation, lithium carbonate, iron phosphate, ammonium dihydrogen phosphate and glucose are dispersed in deionized water and mixed evenly, and then sand milled and spray dried to obtain a lithium iron phosphate precursor, and the above precursor is placed in a sintering furnace, and under a protective N2 atmosphere, the temperature is raised to 770±20°C at a rate of 3°C / min and calcined for 9 to 10 hours to obtain a lithium iron phosphate matrix.

[0047] As an example, the D50 of the nano MoN particles is 50 nm.

[0048] Example 1

[0049] S1: Modifier preparation:

[0050] According to the mass ratio of MoN to TiN nanotubes (thickness, diameter, and length are 12±2nm, 90±10nm, and 350±20nm, respectively) of 0.05:1, nano MoN particles and TiN nanotubes are placed in deionized water (solvent), liquid phase mixed and dried, and then heat treated at 780°C for 7h to obtain MoN / TiN nanotubes (modifier);

[0051] S2: Composite material preparation:

[0052] 50 g of MoN / TiN nanotubes (modifier, prepared in step S1) were pre-dispersed in 1000 g of ethanol (solvent), 400 g of the above-mentioned lithium iron phosphate matrix was weighed and added to the pre-dispersed MoN / TiN nanotubes, stirred for 1 hour, and then spray-dried. The spray-dried material was placed in an atmosphere sintering furnace, and heated to 550° C. at a rate of 3° C. / min under a protective N2 atmosphere, and calcined for 6 hours to obtain a MoN / TiN nanotube cross-linked wrapped nano lithium iron phosphate positive electrode material.

[0053] Example 2

[0054] S1: According to the mass ratio of MoN to TiN nanotubes (thickness, diameter and length are 15±2nm, 40±5nm and 350±20nm respectively) of 0.03:1, nano MoN particles and TiN nanotubes were physically mixed and then heat treated at 800℃ for 6h to obtain MoN / TiN nanotubes.

[0055] S2: 80g of MoN / TiN nanotubes were pre-dispersed in 1100g of methanol, 700g of the above-mentioned lithium iron phosphate matrix was weighed and added to the pre-dispersed MoN / TiN nanotubes, stirred for 0.5h and then spray-dried, and the spray-dried material was placed in an atmosphere sintering furnace, and heated to 500°C at a rate of 3°C / min under a protective N2 atmosphere and calcined for 5h to obtain MoN / TiN nanotube cross-linked wrapped nano lithium iron phosphate positive electrode material.

[0056] Example 3

[0057] Compared with Example 1, the only difference is that the solvent for the liquid phase mixing of nano MoN particles and TiN nanotubes in step S1 is ethanol, and the other operations and parameters are the same as those in Example 1.

[0058] Comparative Example 1

[0059] Compared with Example 1, the only difference is that in step S1, there is no TiN nanotube, and a separate molybdenum nitride modifier is prepared. Other operations and parameters are the same as in Example 1.

[0060] Comparative Example 2

[0061] Compared with Example 1, the only difference is that in step S1, there are no MoN particles, and a separate TiN nanotube modifier is prepared. Other operations and parameters are the same as in Example 1.

[0062] Comparative Example 3

[0063] Compared with Example 1, the only difference is that step S1 is not performed, and the modifier in step S2 is replaced by carbon nanotubes. Other operations and parameters are the same as in Example 1.

[0064] Comparative Example 4

[0065] Compared with Example 1, the only difference is that in step S1, no calcination treatment is performed, that is, the calcination temperature is a drying temperature of 100° C., and other operations and parameters are the same as in Example 1.

[0066] Comparative Example 5

[0067] Compared with Example 1, the only difference is that in step S1, the TiN nanotubes are TiN nanopowder particles (D50 is 51 nm), and other operations and parameters are the same as those in Example 1.

[0068] test

[0069] (1) Preparation of positive electrode sheet:

[0070] The positive electrode materials prepared by the above method in Examples 1 to 3 and Comparative Examples 1 to 5 were used as positive electrode active materials. The positive electrode active materials: SP (superconducting carbon black): PVDF (polyvinylidene fluoride) were homogenized at a mass ratio of 90:5:5 and coated on a 20 μm thick aluminum foil to produce a positive electrode sheet with a surface density of 8 mg / cm 2 , and then through drying, rolling, die cutting, punching into positive electrode sheets.

[0071] (2) Preparation of battery: button cell assembly was performed using R2032 button cell shells, lithium sheet was used as negative electrode, PE material was used as separator, and 80 μL of electrolyte (1 mol / L LiPF6 / EC+DMC (volume ratio = 1:1)) was added. The test temperature was 25°C, the test voltage range of LFP active material was 2.0V to 3.75V, constant current constant voltage charging was used to charge to 3.75V, and constant current discharge was used to discharge to 2.0V; the first four charge and discharge currents were 0.1C, 0.2C, 0.5C, and 1C respectively; in addition, the discharge capacity at low temperature (-20°C), 1C, 2C, 3C, 4C, 5C, and 10C were further tested, and the capacity retention rate was tested at low temperature by 3C / 3C charge and discharge for 100 weeks.

[0072] Table 1 Comparison of electrochemical properties of active materials in Examples 1-3 and Comparative Examples 1-5

[0073]

[0074] Note: Normal temperature refers to 25℃, and low temperature refers to -20℃.

[0075] In summary, the process described in the present invention, the MoN / TiN nanotubes are calcined and cross-linked to wrap nano-lithium iron phosphate, which improves the lithium ion diffusion rate at the lithium iron phosphate interface, reduces the diffusion barrier of Li+, and increases the Li+ diffusion rate, effectively improving the rate discharge capacity and cycle performance of LFP at low temperatures.

[0076] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a MoN / TiN nanotube / lithium iron phosphate composite material, characterized in that: The lithium iron phosphate material and the MoN / TiN nanotubes are mixed and then calcined at a temperature of 300 to 700°C to obtain the mixed material.

2. The method for preparing the MoN / TiN nanotube / lithium iron phosphate composite material according to claim 1, characterized in that: The lithium iron phosphate material is carbon composite lithium iron phosphate.

3. The method for preparing the MoN / TiN nanotube / lithium iron phosphate composite material according to claim 2, characterized in that: The lithium iron phosphate material is obtained by sintering a mixture containing an iron source, a lithium source, a phosphorus source and a carbon source.

4. The method for preparing the MoN / TiN nanotube / lithium iron phosphate composite material according to claim 1, characterized in that: The MoN / TiN nanotube is a hollow tubular material formed by the composite of MoN and TiN, wherein the thickness of the tube is 5-30nm, the diameter of the tube is 50-120nm, and the length of the tube is 150-500nm.

5. The method for preparing the MoN / TiN nanotube / lithium iron phosphate composite material according to claim 1, characterized in that: The MoN / TiN nanotubes are obtained by mixing nano MoN particles and TiN nanotubes and then heat treating at 500-900°C. Preferably, the mass ratio of MoN to TiN is 0.01 to 0.1:1; Preferably, the heat treatment holding time is 4 to 10 hours.

6. The method for preparing the MoN / TiN nanotube / lithium iron phosphate composite material according to claim 1, 4 or 5, characterized in that: The weight ratio of lithium iron phosphate to MoN / TiN nanotubes in the lithium iron phosphate material is 1:0.005-0.1; Preferably, the lithium iron phosphate material and the MoN / TiN nanotubes are composited in a solid phase or liquid phase manner.

7. The method for preparing the MoN / TiN nanotube / lithium iron phosphate composite material according to claim 1, characterized in that: The calcination atmosphere is a protective atmosphere; Preferably, the lithium iron phosphate material and the MoN / TiN nanotubes are composited by a liquid phase method using an organic solvent such as methanol or ethanol; Preferably, the calcination temperature is 400-600°C; Preferably, the holding time at the calcination temperature is 2 to 8 hours.

8. A MoN / TiN nanotube / lithium iron phosphate composite material prepared by the preparation method according to any one of claims 1 to 7.

9. An application of the MoN / TiN nanotube / lithium iron phosphate composite material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: It is used as positive electrode active material to prepare lithium-ion batteries.

10. A lithium ion battery, characterized in that: It comprises a MoN / TiN nanotube / lithium iron phosphate composite material prepared by the preparation method according to any one of claims 1 to 7; Preferably, the positive electrode of the lithium-ion battery comprises the MoN / TiN nanotube / lithium iron phosphate composite material.

Citation Information

Patent Citations

  • Lithium iron phosphate composite positive electrode material with surface coated with titanium nitride and graphene as well as preparation method and application of material

    CN104124437A

  • Lithium iron phosphate composite cathode material as well as preparation method and application thereof

    CN108091851A

  • Preparation method for spherical lithium iron phosphate composite material co-doped with Ti and N

    CN108598383A

Cited By

  • Binder and method for producing same, lithium iron phosphate cathode and method for producing same, lithium ion battery

    CN122587634A